Vitiligo: An Autoimmune Skin Disease and its Immunomodulatory Therapeutic Intervention - Chang, Wei-Ling; Lee, Woan-Ruoh; Kuo, Yung-Che; Huang, Yen-Hua (Frontiers in Cell and Developmental Biology, 2021)
Vitiligo is a chronic autoimmune depigmenting skin disorder characterized by patches of the skin losing functional melanocytes. Multiple combinatorial factors are involved in disease development, among which immune T cells play a prominent role. The immune cells implicated in melanocyte destruction through adaptive immunity include CD8+ cytotoxic T cells and regulatory T cells, and aberrantly activated skin-resident memory T cells also play a role in melanocyte destruction. Over the past several years, major progress in understanding vitiligo pathogenesis has led to the development of targeted therapies. Janus kinase (JAK) inhibitors, which share the similar mechanism that autoactivates CD8+ T cells in chronic inflammatory diseases, have been reported to have therapeutic significance in vitiligo. Recently, immunomodulatory therapeutic interventions in vitiligo have been emerging. Mesenchymal stem cells (MSCs) regulate cytokine secretion and the balance of T-cell subsets, which makes them a promising cell-based treatment option for autoimmune diseases. The induction of MSC-mediated immunomodulation is complicated and occurs by contact-dependent mechanisms and soluble extracellular vesicle (EV) mediators. EVs released from MSCs contain various growth factors and cytokines with anti-inflammatory effects in the skin immune response. Here, we summarize and discuss the progress to date in targeted therapies that immunomodulate the niche environment of vitiligo, from the clinical trial of JAK inhibitors to the potential of MSCs and MSC-EVs. The available information was collected to highlight the need for further research into the treatment of vitiligo.